Minerva's orthography: early colonial projects for print literacy in African languages. (2nd January 2019) - Irvine, Judith T.
ABSTRACT: In sub-Saharan West Africa during the nineteenth century, European missionaries and others sought to promote print literacy among local populations, especially to enable Africans to read religious works in their own languages. Print technology was to offer economies of scale, by reaching wide audiences. Seen, moreover, as an instrument of modernity, print was also supposed to stabilise and improve African languages, deemed wildly unstable, variable, and phonetically uncouth. The work of "reducing a language to writing" required devising orthographies, whose specific forms were driven by the needs of European-based printing. Materials, production processes, translations, and decision-making circulated between colony and metropole in complex patterns in which European audiences usually mattered more than the Africans who were the literacy projects' targets. Comparing British and French areas, Protestants and Catholics, Christians and Muslims, and European scripts and those developed independently by Africans, can illustrate the range of decision makers and the variety of social worlds in which African-language scripts and print cultures have emerged.